2006
DOI: 10.1111/j.2006.0908-8857.03574.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of genetic evidence for identifying intra-specific brood parasitism

Abstract: Intra‐specific brood parasitism is widespread among birds. When genetic evidence is not available, criteria like super‐normal clutch size, high within‐clutch variance in egg morphology, and shorter than normal laying intervals have been used to identify parasitized broods. Here we report genetically determined parentage of a clutch of super‐normal size in a species with fixed clutch size, the northern lapwing Vanellus vanellus. Results from multi‐locus DNA fingerprinting revealed no loss of parentage in this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Special care is also necessary because the majority of descriptions of breeding systems of shorebird species used in the phylogenetic comparative studies were based on interpretations of observed behavior, without genetic support (e.g., MacLean 1969, Nettleship 1973, Gratto-Trevor 1991; but see, e.g., Wallander et al 2001, Blomqvist et al 2002b. Although the breeding biology of some shorebirds has certainly been comprehensively studied, for example, in the Kentish Plover (Charadrius alexandrinus; Küpper et al 2004), Red-necked Phalarope (Phalaropus lobatus; Schamel et al 2004), and Northern Lapwing (Vanellus vanellus; Grønstøl et al 2006), more data are needed on genetic mating systems and intraspecific variation in breeding decisions in most shorebirds .…”
Section: Discussionmentioning
confidence: 99%
“…Special care is also necessary because the majority of descriptions of breeding systems of shorebird species used in the phylogenetic comparative studies were based on interpretations of observed behavior, without genetic support (e.g., MacLean 1969, Nettleship 1973, Gratto-Trevor 1991; but see, e.g., Wallander et al 2001, Blomqvist et al 2002b. Although the breeding biology of some shorebirds has certainly been comprehensively studied, for example, in the Kentish Plover (Charadrius alexandrinus; Küpper et al 2004), Red-necked Phalarope (Phalaropus lobatus; Schamel et al 2004), and Northern Lapwing (Vanellus vanellus; Grønstøl et al 2006), more data are needed on genetic mating systems and intraspecific variation in breeding decisions in most shorebirds .…”
Section: Discussionmentioning
confidence: 99%
“…This approach has therefore been applied (although with caveats) for the identification of parasitic eggs in some conspecific brood parasite species (Gibbons, 1986; Møller, 1987; Jackson, 1992; Petersen, 1992; Bruce E. Lyon, 1993; McRae & Burke, 1996; B. E Lyon, 2003). However, some studies that estimated accuracy of parasitic egg identification showed ambiguous results for some species (Ådahl, Lindström, Ruxton, Arnold, & Begg, 2004; Pöysä, Lindblom, Rutila, & Sorjonen, 2009; Eadie, Smith, Zadworny, Kühnlein, & Cheng, 2010; Lemons, Sedinger, & Randle, 2011; Petrželková, Pöysä, Klvaňa, Albrecht, & Hořák, 2017) and for others this method did not work at all (Brown & Sherman, 1989; Cariello, Lima, Schwabl, & Macedo, 2004; Grønstøl, Blomqvist, & Wagner, 2006; Griffith, Barr, Sheldon, Rowe, & Burke, 2009; Roy, Parker, & Gates, 2009). One of the reasons why many studies found low accuracy of identification might be that closely related females lay indistinctive eggs.…”
Section: Introductionmentioning
confidence: 99%